Indonesianisasi Islam: Penguatan Islam Moderat dalam Lembaga Pendidikan Islam di Indonesia - Toto Suharto (IAIN Ponorogo, 2017)
Abstract: The history records that Islam entered Indonesia conducted through peaceful Da’wa. This peaceful Da’wa has given birth to the moderate Islam for Indonesian. The moderate Islam is the character of Indonesian Islam distinct from Islam elsewhere in the world. However, this character of the moderate Islam began to be challenged, since the transnational Islamic organizations into Indonesia. Here the ideological struggle occurred between Indonesianization of Islam and Islamisation of Indonesia. This article presents that Islamic education is an instrument of the most strategic in strengthening the moderate Islam that became the main character of Islam in Indonesia. The Islamic education organized by Islamic educational institutions of Indonesia typically, for sure, teach the learners about Indonesian Islam with its moderate character. At the same time, transnational Islamic educational institutions were trying to do Islamization of Indonesia to the learners. This struggle necessitates the importance of strengthening the role of Islamic educational institutions in conducting Indonesianization Islam so that moderate Islam can be maintained in the Archipelago.الملخص: سجّل البيان التاريخي أن الإسلام جاء إلي إندونيسيا علي سبيل الدعوة السِّلمية. وقد تولّدت من هذه الدعوة السِّلمية السمة الوسطيّة للإسلام الإندونيسي. وصارت هذه السمة الوسطية من مميّزات الإسلام الإندونيسي التي تخالف عن الإسلام في أي مكان آخر في هذا العالم. ومع ذلك، فإن هذه السمة للإسلام الإندونيسي قد واجهت هذه الأيام عدّة تحدّيّات لاسيما بمجيء المنظمات الإسلامية عبر الوطنية في إندونيسيا، حتي يحدث الآن في هذا البلد المحبوب ما يسمي بالطعن الأيديولوجي بين نموذج